Constructivist governance of the Internet - Mazurier, Pablo A.; Delgado Moran, Juan José; Payá Santos, Claudio (Teoría y Praxis, 2022)
The purpose of this paper is to study the configuration of a specific type of leadership that has developed within the innovative Internet governance regime. Framed in the postulates of the constructivist current of International Relations, this leadership is characterized by being of a discursive and collaborative type, since it bases its power on the discourse and values it promotes, while ensuring the joint, harmonious and polycentric work of all the interested actors in order to realize the common interest on the internet. This will be demonstrated through the discursive and management analysis carried out by two high institutional references of the internet ecosystem in this decade: Kathryn Brown of ISOC and Fadi Chehadé of ICANN.